An advanced glycation endproduct (AGE)‐rich diet promotes accumulation of AGEs in Achilles tendon. Issue 6 (29th March 2017) - Skovgaard, Dorthe; Svensson, Rene B.; Scheijen, Jean; Eliasson, Pernilla; Mogensen, Pernille; Hag, Anne Mette F.; Kjær, Michael; Schalkwijk, Casper G.; Schjerling, Peter; Magnusson, Stig P.; Couppé, Christian
Abstract: Advanced Glycation Endproducts (AGEs) accumulate in long‐lived tissue proteins like collagen in bone and tendon causing modification of the biomechanical properties. This has been hypothesized to raise the risk of orthopedic injury such as bone fractures and tendon ruptures. We evaluated the relationship between AGE content in the diet and accumulation of AGEs in weight‐bearing animal Achilles tendon. Two groups of mice (C57BL/6Ntac) were fed with either high‐fat diet low in AGEs high‐fat diet (HFD) ( n = 14) or normal diet high in AGEs (ND) ( n = 11). AGE content in ND was six to 50‐fold higher than HFD. The mice were sacrificed at week 40 and Achilles and tail tendons were carefully excised to compare weight and nonweight‐bearing tendons. The amount of the AGEs carboxymethyllysine (CML), methylglyoxal‐derived hydroimidazolone (MG‐H1) and carboxyethyllysine (CEL) in Achilles and tail tendon was measured using ultraperformance liquid chromatography tandem mass spectrometry (UPLC‐MS/MS) and pentosidine with high‐pressure liquid chromatography (HPLC) with fluorescent detection. AGEs in Achilles tendon were higher than in tail tendon for CML ( P < 0.0001), CEL ( P < 0.0001), MG‐H1 and pentosidine (for both ND and HFD) ( P < 0.0001). The AGE‐rich diet (ND) resulted in an increase in CML ( P < 0.0001), MG‐H1 ( P < 0.001) and pentosidine ( P < 0.0001) but not CEL, in Achilles and tail tendon. This is the first study to provide evidence for AGE accumulation in injury‐prone, weight‐bearing Achilles tendon associated with intake of an AGE‐rich diet. This indicates that food‐derived AGEs may alter tendon properties and the development of tendon injuries. Abstract : This is the first study to provide evidence for advanced glycation endproduct (AGE) accumulation in injury‐prone, weight‐bearing Achilles tendon associated with intake of an AGE‐rich diet. This indicates that food‐derived AGEs may alter tendon properties and the development of tendon injuries.